Polymer Science: From Basics to Nanotechnology Applications: Ilmu Polimer: Dari Dasar hingga Nanoteknologi Aplikasi - Hiba Fouad Tawfeeq Wali; Saja Abdul Ameer Sayed; Ahmed A. Thamer (Academia Open, 2026)
General Background: Polymer materials have become essential components in modern technology due to their lightweight structure, chemical stability, and adaptable physical characteristics. Specific Background: Advances in polymer science have enabled the modification of molecular structures and the integration of nanoparticles, allowing polymers to perform functions beyond traditional insulating and structural roles. Knowledge Gap: Despite extensive use in industrial and technological fields, a comprehensive conceptual synthesis linking polymer structure, classification, properties, and emerging nanotechnology applications remains necessary to clarify their functional relationships. Aims: This study analyzes the fundamental principles of polymer science, including structural composition, polymerization mechanisms, classifications, and key physical and chemical properties, while highlighting emerging nanopolymer applications. Results: The analysis demonstrates that polymer performance is strongly related to molecular structure, degree of polymerization, and intermolecular interactions. The integration of metal and oxide nanoparticles within polymer matrices introduces additional optical, electrical, and catalytic functionalities. Novelty: The work provides an integrated conceptual overview connecting classical polymer theory with modern nanocomposite developments in materials science. Implications: Understanding the structure–property relationship of polymers supports the development of advanced materials for applications in electronics, renewable energy systems, biosensors, and biomedical technologies, while also emphasizing the importance of sustainable polymer research. Keywords: Polymer Science, Nanopolymer Materials, Polymer Structure, Polymer Nanocomposites, Materials Engineering Key Findings Highlights Polymer molecular structure determines mechanical, thermal, and electrical material behavior. Nanoparticle integration introduces new optical and electronic functionalities in polymer systems. Polymer nanocomposites support emerging technologies in energy systems, sensing devices, and biomedical materials.